The children - Henao-Hidrón, Javier (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Children -the neutral gender includes both genders-represent articulating center of a civilized society, the most beautiful expression of human life, the greatest source of joy for adults... they are present and future, and should have primacy in government programs, since nothing as just and important as the comprehensive protection of their dignity.